The Allegory of Political Violence in Sony Labou Tansi’s Life and a Half - Manizha Sepas (Janeway JS, 2020)
An embodied reading of Sony Labou Tansi's absurdism which functions as a tool for discoursing colonisation, state violence and the hypersexual masculinity of power as symbolised through the metaphor of cannibalism.